1991
DOI: 10.1590/s0074-02761991000600018
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effect of alkaloids

Abstract: Because of the increased use of alkaloids in general medical practice in recent years, it is of interest to determine genotoxic, mutagenic and recombinogenic response to different groups of alkaloids in prokaryotic and eucaryotic organisms. Reserpine, boldine and chelerythrine did not show genotoxicity response in the SOS-Chromotest whereas skimmianine showed genotoxicity in the presence of a metabolic activation mixture. Voacristine isolated from the leaves of Ervatamia coronaria shows in vivo cytostatic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…It has been suggested that alkaloids are potentially mutagenic, because their therapeutic actions involve interactions with DNA [4,[40][41][42]. This possibility was corroborated in the present study only when mice were submitted to the highest dose of isatin (150 mg/kg b.w.)…”
Section: Discussionsupporting
confidence: 83%
“…It has been suggested that alkaloids are potentially mutagenic, because their therapeutic actions involve interactions with DNA [4,[40][41][42]. This possibility was corroborated in the present study only when mice were submitted to the highest dose of isatin (150 mg/kg b.w.)…”
Section: Discussionsupporting
confidence: 83%
“…The mechanisms of its action included the suppression of TNF -α and IL -6 gene transcription, the inhibition of the production of NO, prostaglandin E2, and superoxide anions, as well as elastase-release [ 1 , 10 , 11 ]. Furthermore, skimmianine also exhibited cytotoxicity against a variety of cancer cell lines [ 12 , 13 , 14 , 15 ] and genotoxicity [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chelerythrine-induced disintegration of the mitochondrial genome in S. cerevisiae, demonstrated for the first time in this paper, can be explained by the intercalative binding of the alkaloid to mitochondrial DNA [9]. This mutagenic effect of chelerythrine in yeast is in contrast to a recent study failing to demonstrate its genotoxic and mutagenic activity in Escherichia coli [13] and should be taken into consideration for the longterm medical use of this phytotherapeutic.…”
Section: Omentioning
confidence: 88%